New method for estimating the refractive index of optical materials in spectrally selective elements - Manko, A.A.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
A numerical simulation of the scattering indicatrix in optical spectral-selective cylindrical form elements has been performed. As it follows from the results of the calculations, the shape of the scattering indicatrix of these elements is unambiguously determined by the refractive index of material from which they are made. Location of angular peaks in the indicatrix in combination with its shape allows to estimate the refractive index with sufficiently high degree of accuracy.